Factors influencing knowledge and behaviors related to food safety during purchasing among consumers in Libya - Abuhlega, Thuraya Ahmed; Abduljalil, Aya Anwar (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Libyan consumers mainly rely on purchasing food products and preparing them at home. Therefore, knowing the rules of food safety when purchasing is key to protect them from foodborne diseases. This study aims to assess food safety knowledge and behaviours during purchasing among consumers in Libya. Method: The study was carried out through the internet by Qsurvey and filling paper questionnaires by self-administration method to explore the level of food safety knowledge and practices during purchasing among consumers in Libya, from March to December 2020. Data were analyzed by SPSS. A Chi-square test was used to determine the influence of demographics on the level of knowledge and behaviours. Bivariate correlation coefficient analysis was used to determine the correlation between knowledge and behaviours scores. A p value of <0.05 was considered statistically significant. Result: There was a total of 1027 consumers surveyed. A good level of food safety knowledge was found in 531(51.7%) and the level of food safety behaviours was moderate in 684(66.6%). The age and monthly income influence food safety knowledge (P<0.05) while gender and age influence food safety behaviour during purchasing (P<0.05). Conclusion: The level of food safety knowledge was good and the level of behaviours was only moderate. Therefore, there is a need to raise awareness of the population related to food safety.